2021
DOI: 10.3390/children8111022
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Physical Activity and Mental Health in Iranian Adolescents during the COVID-19 Pandemic: An Accelerometer-Based Study

Abstract: Using self-reported questionnaires, several studies found that social isolation during the COVID-19 pandemic has significantly changed the level of physical activity (PA) in children and adolescents. Since the objectivity of self-reported PA is limited in several ways, we used modern accelerometers in this study to assess the PA levels of male and female adolescents during the pandemic-related lockdown. Moreover, the association of PA with mental health of the adolescents were analyzed. A total of 136 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
1
10
0
3
Order By: Relevance
“…Higher physical activity and less sedentary behavior were the significant predictors of good well-being in adolescence, supporting the existing evidence-based results suggesting that these are very important for keeping youth in a good health and good mood [23], especially in high-income countries [17]. The current study, as well as other studies, reports high proportions of the adolescents not being sufficiently physically active and/or showing an excessive duration of passive screen time during the pandemic [13,19,20,42] and pre-pandemic [10,11,17,[21][22][23]32] periods. These findings are particularly concerning.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Higher physical activity and less sedentary behavior were the significant predictors of good well-being in adolescence, supporting the existing evidence-based results suggesting that these are very important for keeping youth in a good health and good mood [23], especially in high-income countries [17]. The current study, as well as other studies, reports high proportions of the adolescents not being sufficiently physically active and/or showing an excessive duration of passive screen time during the pandemic [13,19,20,42] and pre-pandemic [10,11,17,[21][22][23]32] periods. These findings are particularly concerning.…”
Section: Discussionsupporting
confidence: 89%
“…To note, Lithuania and several other Nordic countries are regions with unfavorable conditions to have sports activities outdoors in autumn, winter, and early spring of 2021, the periods which were restricted for any indoor sports activities for most adolescents during the second lockdown. Therefore, it should be ensured that children and adolescents still have access to sport and exercise during possible future periods of closure [ 19 ], for example, by maintaining sports clubs and sports facilities that comply with the existing COVID-19 rules [ 20 ]. Our previous studies also revealed that after controlling for sociodemographic factors, youths’ leisure physical activity was related to higher accessibility to physical activity resources, neighborhood safety, family social capital, and to the greater social network and social participation, implying that the interventions should include a community’s social and physical environmental changes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…as well as prevents various diseases (e.g., cardiovascular disease, diabetes, cancer, osteoporosis, etc.) in different age-groups, including children [10,15,16,19,25,30,41]. Accordingly, the World Health Organization (WHO) recommended that children aged 6 to 17 years should participate in at least 60 minutes of moderate-to-vigorous physical activity (MVPA) every day of the week [5].…”
Section: Introductionmentioning
confidence: 99%